Vegetation history - Carter, Stephen; Dalland, Magnar; Long, Deborah (Scottish Archaeological Internet Reports, 2005)
The archaeological programme was supported by palaeoenvironmental studies. A deep peat basin was identified during the initial archaeological survey of the roadline at Allt Dail an Dubh-asaidh. A peat core was extracted from this site and analysed to provide a high-resolution record (both spatial and temporal) of the vegetation of that area. These results provide detailed data on only one part of the Arisaig landscape. Fortunately, there are pollen diagrams from four other locations in or very close to Arisaig that can be used to assess variations in landscape history across this area.